Bioaccessibility and Antioxidant Capacity of Bioactive Compounds From Various Typologies of Canned Tomatoes - Izzo, Luana; Castaldo, Luigi; Lombardi, Sonia; Gaspari, Anna; Grosso, Michela; Ritieni, Alberto (Frontiers in Nutrition, 2022)
Tomato (Solanum lycopersicum L.) is one of the most consumed vegetables in the world; it contains high amounts of antioxidant phytochemicals and essential nutrients. Although it is commonly consumed fresh, more than 80% of its consumption derives from processed products. Since limited information on changes in the bioaccessibility of bioactive compounds during gastrointestinal digestion was reported, this current study aimed to monitor the antioxidant activity, total polyphenolic and carotenoid content, and bioaccessibility during in vitro gastrointestinal digestion of different typologies (n = 7) of canned tomatoes. A comprehensive evaluation of the polyphenolic profile of digested and not digested samples was ascertained by ultra-high-performance liquid chromatography combined with high-resolution Orbitrap mass spectrometry. The results highlighted a considerable content of rutin (1.191–9.516 mg/100 g), naringenin (0.359–1.452 mg/100 g), chlorogenic acid (1.857–11.236 mg/100 g), and lycopene (50.894–222.061 mg/kg) in the analyzed matrices. After in vitro gastrointestinal digestion, large variability, losses and low recovery were recorded. An appreciable percentage of rutin (30.7%), naringenin (29.6%), chlorogenic acid (25.8%), and lycopene (varied between 9.3 and 20%) remained bioaccessible after the in vitro gastrointestinal digestion. Our study could be a valid support to evaluate which content of bioactive compounds could be really bioaccessible to exercise beneficial effects on human health.